Implementasi Metode Waterfall Pada Sistem Informasi Geografis Tata Ruang - Redho Harli Saputra; Nur Rochmah Dyah P.A (Journal of Information System Research (JOSH), 2023)
This research aims to develop a web-based Geographic Information System (GIS) using the waterfall method to overcome the limited information available to the public regarding building and spatial licensing in Bengkulu City. The development method used is the waterfall method, which includes the stages of analysis, design, implementation, testing, and maintenance. The test results show that this system provides easy access to accurate and timely information to the community. Black box testing showed high reliability and stability, with no failures or errors in system functionality. In addition, usability testing involved 42 respondents from the Bengkulu city community, who gave a high level of satisfaction with the user interface, ease of use, and quality of information presented by the system. Thus, this research contributes to the efficient and transparent management of building and spatial licensing in Bengkulu City, and can be a reference for relevant agencies in providing information that is easily accessible and meets the needs of the community.